2007
DOI: 10.1128/jcm.01918-06
|View full text |Cite
|
Sign up to set email alerts
|

First Molecular Epidemiology Study ofMycobacterium tuberculosisin Burkina Faso

Abstract: We conducted a molecular epidemiology study on 120 Mycobacterium tuberculosis isolates from patients presenting pulmonary tuberculosis (TB) in Burkina Faso. Classical antibiogram studies and genetic characterization, using mycobacterial interspersed repetitive-unit-variable-number tandem-repeat (MIRU-VNTR) typing and spoligotyping, were applied after culture. Molecular analysis of specific signatures showed that all TB cases reported in this study were caused by M. tuberculosis and identified no Mycobacterium … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

10
55
3

Year Published

2010
2010
2021
2021

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 72 publications
(68 citation statements)
references
References 27 publications
(31 reference statements)
10
55
3
Order By: Relevance
“…It was also observed in the same previous study (Cadmus et al, 2006) that 69% of the M. tuberculosis isolates were of the CAM family, compared to the present observation that 56% of M. tuberculosis strains which were spoligotyped were of the CAM family. The CAM family was also found in Burkina-Faso (Godreuil et al, 2007), Sierra Leone (Homolka et al, 2008), Niger, Ivory Coast as well as in several parts of Europe particularly France ) and they appear to be the dominant M. tuberculosis strain circulating in Nigeria.…”
Section: Discussionmentioning
confidence: 99%
“…It was also observed in the same previous study (Cadmus et al, 2006) that 69% of the M. tuberculosis isolates were of the CAM family, compared to the present observation that 56% of M. tuberculosis strains which were spoligotyped were of the CAM family. The CAM family was also found in Burkina-Faso (Godreuil et al, 2007), Sierra Leone (Homolka et al, 2008), Niger, Ivory Coast as well as in several parts of Europe particularly France ) and they appear to be the dominant M. tuberculosis strain circulating in Nigeria.…”
Section: Discussionmentioning
confidence: 99%
“…The analysis also shows that M. africanum seems to be disappearing in Cameroon, a Central African country, unlike in West African countries, which continue to report between 20% and 39% of cases attributable to this species (7,(10)(11)(12)(13). Previous studies have raised potential limitations concerning the difficulties in isolating and identifying M. africanum due to metabolic constraints (14) and the bias that may have characterized studies that concluded that M. africanum was regressing in Africa (11).…”
mentioning
confidence: 91%
“…M. bovis, M. tuberculosis or other) was not recorded. A more recent study from the same country [15] failed to find M. bovis in 120 samples of sputum that were positive for Mycobacterium spp., although it should be noted that most of the cases were from urban areas (where direct contact with cattle is less likely). A recent study from Mexico might also provide some evidence of aerosol transmission [16].…”
Section: Glossarymentioning
confidence: 99%